Effectiveness of plyometric training vs. complex training on the explosive power of lower limbs: A Systematic review - Wang, X.; Lv, C.; Qin, X.; Ji, S.; Dong, D. (Frontiers in Physiology, 2023)
Introduction: Explosive power is considered an important factor in competitive events. Thus, strategies such as complex training (CT) and plyometric training (PLT) are effective at improving explosive power. However, it is still not clear which of the two strategies can enable greater improvements on the explosive power. Thus, the aim of this systematic review was to compare the effects of PLT and CT on the explosive power of the lower limbs.